2012
DOI: 10.1128/jvi.06325-11
|View full text |Cite|
|
Sign up to set email alerts
|

A Human CD4+T Cell Epitope in the Influenza Hemagglutinin Is Cross-Reactive to Influenza A Virus Subtypes and to Influenza B Virus

Abstract: The hemagglutinin protein (HA) of the influenza virus family is a major antigen for protective immunity. Thus, it is a relevant target for developing vaccines. Here, we describe a human CD4 + T cell epitope in the influenza virus HA that lies in the fusion peptide of the HA. This epitope is well conserved in all 16 subtypes of the HA protein of influenza A virus and the HA protein of influenza B virus. By stimulating peripheral blood mononuclear cells (PBMCs) from a healthy adult donor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 82 publications
(76 reference statements)
0
26
0
3
Order By: Relevance
“…In this study we used TIV and it was surprising to see that the serum response against the Influenza B/Brisbane/60/08 (WHO-Victoria-like influenza B) antigen was so strong also without any adjuvant. Previously studies have shown that there is cross-reactive antibody and CD4+ T cell responses between influenza B and A HAs in both humans and mice [32], [33], [34] and there is an estimated 23–27% amino acid homology between influenza B and A HA proteins [34], [35], [36]; which may be a reason for a strong IgG response towards influenza B. Also, in close proximity to the fusion peptide in the stalk of the HA, a highly conserved B cell epitope have been identified and shown to be cross-reactive within influenza A subtypes and influenza B HA [37].…”
Section: Discussionmentioning
confidence: 99%
“…In this study we used TIV and it was surprising to see that the serum response against the Influenza B/Brisbane/60/08 (WHO-Victoria-like influenza B) antigen was so strong also without any adjuvant. Previously studies have shown that there is cross-reactive antibody and CD4+ T cell responses between influenza B and A HAs in both humans and mice [32], [33], [34] and there is an estimated 23–27% amino acid homology between influenza B and A HA proteins [34], [35], [36]; which may be a reason for a strong IgG response towards influenza B. Also, in close proximity to the fusion peptide in the stalk of the HA, a highly conserved B cell epitope have been identified and shown to be cross-reactive within influenza A subtypes and influenza B HA [37].…”
Section: Discussionmentioning
confidence: 99%
“…This approach may therefore be a good candidate for generating adaptive memory responses at the site of infection that are capable of limiting the replication of heterotypic viruses, particularly if well-conserved epitopes were chosen for vaccination. To that end, Babon et al (165) identified a CD4 T cell epitope in the fusion peptide of the HA that is conserved across all influenza A HA subtypes as well as the influenza B HA protein. A CD4 T cell clone recognizing this epitope exhibits cytotoxicity to a variety of influenza strains, including avian H5N1 virus.…”
Section: Vaccine-induced Cd4 Ctlmentioning
confidence: 99%
“…Otherwise, specific CD4 + T cell responses were proven to be indispensable for the clearance of IAV in both animal models (8, 9) and in human volunteers (10). CD4 + T cells can exert their protective effect directly through cytotoxic activity (11) or indirectly through providing “help” to both CD8 + T cells and B-cells to eliminate virus and virus-infected cells via cytotoxicity and antibody neutralization, respectively (12, 13). Furthermore, the generation of strong memory CD4 + and CD8 + T cell responses are also CD4 + helper T cell dependent (14, 15).…”
Section: Introductionmentioning
confidence: 99%